Hubungan Gambaran Diri Ibu Primigravida Dengan Inisiasi Menyusu Dini di Wilayah Puskesmas Lubuk Buaya Kota Padang - Vetty Priscilla (Fakultas Keperawatan Universitas Andalas, 2014)
A Physical change is one of the changes experienced by mothers during pregnancy such as associated with self-image. It means how the mother looked at herself during pregnancy. If the mother does not adapt to these changes it will be affected subsequent to maternal behaviors such as breastfeeding is not immediate. This study aims to see a correlation between self-image of primigravida with early initiation of breastfeeding practice. This research was conducted on 32 respondents by using the cross-sectional methods. Data was taken by a purposive sampling. Data were analyzed by using computerized to analyze the univariate and bivariate analysis. The study was found that 90.6% mothers did not perform early initiation of breastfeeding, while 53.1%have a positive self-image during pregnancy. Then, it is a significant relationship between self-image of primigravida with giving early initiation of breastfeeding where p = 0.001. To improve on giving early initiation of breastfeeding, mother should be given health education about the importance of breastfeeding immediately after birth.